The reading-guiding-muraja'ah method as a learning strategy for yellow books in islamic boarding schools in south west aceh - M. Reza Assiffi; Syibran Mulasi; Masni; Riyan Darwis (At Turots: Jurnal Pendidikan Islam, 2025)
This study analyzes the application of the (Read, Guide, Muraja'ah) Method in the learning of yellow books in Islamic boarding schools in the Southwest Aceh region as a response to the weakening of students' Arabic language skills, increasing dependence on translated books, and the challenges of modernization that affect the quality of classical text comprehension. Through the Read stage to train phonetic accuracy, the Guidance stage to provide correction and conceptual understanding, and the Muraja'ah stage to strengthen memory, this method is considered capable of improving reading accuracy, understanding of meaning, motivation, and discipline of students. A qualitative descriptive approach is used to explore the learning process in depth. The validation results show that aspects of all three methods are in the "very feasible" category, although this study is limited by the variation in student abilities and the time limit for muraja'ah. This study is based on classical Islamic boarding school studies and international pedagogical theories such as scaffolding and guided learning for the effectiveness of the Method. And the findings also confirm the relevance of the Method in bridging classical scientific traditions with the needs of Islamic boarding school learning in the modern era.